2016
DOI: 10.1007/s11663-016-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Treatment on Cold-Sprayed Titanium Coatings: Numerical Modeling and Experimental Analysis

Abstract: In this paper, a selective laser post-deposition on pure grade II titanium coatings, cold-sprayed on AA2024-T3 sheets, was experimentally and numerically investigated. Morphological features, microstructure, and chemical composition of the treated zone were assessed by means of optical microscopy, scanning electron microscopy, and energy dispersive X-ray spectrometry. Microhardness measurements were also carried out to evaluate the mechanical properties of the coating. A numerical model of the laser treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with the aluminium substrate, the oxygen percentage decreases to characteristic values of titanium grade 2. It should be noted that the XRD analysis of the treated surface, presented by the authors in a previous paper [32], confirmed the formation of a rutile layer as well as a thick oxygen diffused zone underlying the oxidised zone. This result will be useful in the further discussion of the results.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with The relative concentration of two elements (Ti, O), in the topmost layer of the cross-section, is approximately equal to the stoichiometric one for the titanium dioxide; moving to the interface with the aluminium substrate, the oxygen percentage decreases to characteristic values of titanium grade 2. It should be noted that the XRD analysis of the treated surface, presented by the authors in a previous paper [32], confirmed the formation of a rutile layer as well as a thick oxygen diffused zone underlying the oxidised zone. This result will be useful in the further discussion of the results.…”
Section: Resultssupporting
confidence: 57%
“…It should be noted that the XRD analysis of the treated surface, presented by the authors in a previous paper [32], confirmed the formation of a rutile layer as well as a thick oxygen diffused zone underlying the oxidised zone. This result will be useful in the further discussion of the results.…”
Section: Resultssupporting
confidence: 57%
“…The results of the experimental analysis demonstrated the key role played by the aluminum substrate and the ratio between the coating and substrate thickness (also called thickness ratio, TR). Indeed, once the heat input provided by the laser source is fixed, the temperature is governed by the cooling action exerted by the aluminum substrate being more conductive than the titanium [14,16]. Thermal analysis of the laser surface processing pointed out that the peak temperature experienced by the surface and the cooling rate significantly influenced the formation of titanium oxides with good mechanical and wear properties and a satisfactory adhesion with the underlying untreated coating [8,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, once the heat input provided by the laser source is fixed, the temperature is governed by the cooling action exerted by the aluminum substrate being more conductive than the titanium [14,16]. Thermal analysis of the laser surface processing pointed out that the peak temperature experienced by the surface and the cooling rate significantly influenced the formation of titanium oxides with good mechanical and wear properties and a satisfactory adhesion with the underlying untreated coating [8,14,16,17]. In addition, the thermal model developed in the previous investigation was able to predict the formation of distinct microstructures inside the coating, pointing out a tight correlation between the estimated temperature fields and the developed metallurgical zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation